Optimalisasi Kesehatan ODHIV melalui Pendekatan Model Information, Motivation, Behavioral Skills (IMB) - Wardani, Hartati Eko; Sulistina, Dewi Ratna; Hasanah, Winny Kirana; Novembriani, Rizqie Putri; Suprobo, Nina Rini; Azmi, Izzatsaltsa Maya; Retyani, Amira Muradah; Fitriyani, Nasywa (Universitas Muhammadiyah Prof. DR. Hamka (UHAMKA Press), 2025)
Background: Data from 2023 shows that around 39.9 million people in the world are living with HIV. East Java Province is in second place with 77,447 cases of people living with HIV/AIDS in 2022. People with HIV (PLHIV) need social support for treatment, care, and building resilience. Without this support, they are at risk of experiencing declining health, difficulty accessing care, loss of enthusiasm, and feelings of helplessness. Methods: This activity was carried out using the Information, Motivation, Behavioral Skills (IMB) Model approach through counseling by two expert speakers. Supporting media in the form of pocket books were also distributed to participants. The activity was carried out on August 3, 2024, targeting peer supporters from the Mahameru Foundation, Malang City branch and representatives of field outreach from Malang City and Regency. The evaluation was carried out by comparing the results of the pre-test and post-test of the participants. Results: There was an increase in the average pre-test and post-test scores of 13 points. Paired T-Test showed a significant difference between the average pre-test and post-test scores after being given education (p=0.006). The T-test results showed that T count was greater than T table, indicating a significant difference. Conclusions: This counseling program successfully increased participants' knowledge about handling HIV/AIDS and effective communication with PLHIV. To strengthen the role of peer supporters, additional training such as Psychological First Aid is needed to improve skills in providing appropriate emotional support.